Nymphea Water Lily, Trinidad, La Vega Estate, Gran Couva, Trinidad - Martin, Barbara (Unimax Distributors Limited, 2009)
A close-up photograph of a Nymphea Water Lily in bloom sticking out of the water. Postcard number 208.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Nymphaea--Trinidad and Tobago; Water lilies--Trinidad and Tobago; Plants--Trinidad and Tobago; Aquatic plants----Trinidad and Tobago; Water gardens--Trinidad and Tobago; Gardens--Trinidad and Tobago